2022
DOI: 10.48550/arxiv.2202.08850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The fate of observers in circular motion

Antoine Lehébel,
Vitor Cardoso

Abstract: In Newtonian physics or in general relativity, energy dissipation causes observers moving along circular orbits to slowly spiral towards the source of the gravitational field. We show that the loss of energy has the same effect in any theory of gravity respecting the weak equivalence principle, by exhibiting an intimate relation between the energy of a massive test particle and the stability of its orbit. Ultimately, massive particles either plunge, or are driven towards minima of the generalized Newtonian pot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Obviously, for a black hole, its spin must be a/M ∈ (0, 1). From (19), the effective potential V can be obtained, and e 1,2 are given by…”
Section: A Effective Potentialmentioning
confidence: 99%
“…Obviously, for a black hole, its spin must be a/M ∈ (0, 1). From (19), the effective potential V can be obtained, and e 1,2 are given by…”
Section: A Effective Potentialmentioning
confidence: 99%
“…In Refs. [22,23], it was found that an unstable (stable) LR delimits a region of unstable (stable) TCOs radially above (below) it. Moreover, the corresponding corollary was discussed for both horizonless ultracompact objects and black holes.…”
Section: Introductionmentioning
confidence: 99%